Risk for Invasive Cancers in Women With Breast Cancer In Situ: Results From a Population Not Covered by Organized Mammographic Screening - Karavasiloglou, Nena; Matthes, Katarina L.; Pestoni, Giulia; Limam, Manuela; Korol, Dimitri; Wanner, Miriam; Rohrmann, Sabine (Frontiers in Oncology, 2021)
Background Even though breast cancer in situ (BCIS) incidence has been increasing, the prognosis of BCIS patients has not been extensively investigated. According to the literature, women with BCIS have a higher risk of developing subsequent invasive breast cancer; conflicting information has been reported regarding their potential risk for a subsequent invasive non-breast cancer. Methods Data from 1,082 women, whose first-ever cancer diagnosis was primary BCIS between 2003 and 2015 and were living in the canton of Zurich, were used. Standardized incidence ratios (SIRs) were calculated to compare the risk of an invasive breast or non-breast cancer among women with a primary BCIS with the corresponding risk of the adult female population. SIRs were calculated overall and by patient and tumor characteristics. To investigate potential risk factors (e.g., age at diagnosis, treatment) for a subsequent invasive breast or non-breast cancer we used Cox proportional hazards regression models. Results BCIS patients had 6.85 times [95% confidence interval (CI): 5.52–8.41] higher risk of being diagnosed with invasive breast cancer compared to the general population. They additionally faced 1.57 times (95% CI: 1.12–2.12) higher risk of an invasive non-breast cancer. The SIRs were higher for women < 50-years old for both invasive breast and non-breast cancer at BCIS diagnosis. Age ≥ 70-years old at BCIS diagnosis was statistically significantly associated with a subsequent invasive non-breast cancer diagnosis. Conclusions BCIS patients had a higher risk of being diagnosed with invasive breast and non-breast cancer compared to the general population. Age 70 years or older at BCIS diagnosis was the only risk factor statistically significantly associated with a subsequent invasive non-breast cancer. Our results support the increased risk for subsequent cancers in BCIS patients reported in the literature. Future studies should establish the risk factors for subsequent cancers, highlight the need for intensive monitoring in this population, and help distinguish BCIS patients who could benefit from systemic therapy to prevent distant cancers.